Organ donation and transplantation in Mexico. A transplantation health professionals' perspective - Luis Eduardo Hernández-Ibarra; Francisco Javier Mercado-Martínez; Anabel Martínez-Castañeda (Instituto Nacional de Salud Pública, 2017)
Objective. We aimed to explore organ donation and transplantation in Mexico from the point of view of transplantation health professionals. Materials and methods. A qualitative study was carried out. Twenty six organ transplantation health professionals from seven states of Mexico participated. Semi-structured face-to-face interviews were conducted mainly in hospital settings. Critical discourse analysis was performed. Results. According to participants, living organ transplantation offers benefits for recipients as well as for donors. Several factors influence the field of transplantation negatively, among them the scarcity of resources that impedes the incorporation of new health personnel, as well as conflicts between transplantation teams with diverse health professionals and authorities. Conclusion. Besides increasing economic resources, transplantation health personnel should be sensitized to find solutions in order to avoid conflicts with different health professionals. Studies on organ donation and transplants also should include other social actors' viewpoint.